Visually-guided Reaching Under Varying Cognitive and Motor Demand in Young Adult Females with a History of Concussions - (:unkn) unknown (My University, 2017)
Every day, vision guides one’s actions to help one successfully navigate through a complex environment. When our visual and motor systems interact efficiently, we may not fully appreciate how flawless and beneficial this process can be to our daily functioning. Yet, one’s available neural resources needed to successfully perform visually-guided movements do have limits. When an individual suffers a brain injury, such as a concussion, the available resources may be compromised. Examining the extent of this decreased resource pool requires challenging the cognitive abilities enough to observe a behavioral deficit. The purpose of this study was to examine the long-term effects of a history of concussions in young adult females on visuomotor behavior during a visually-guided reaching task of various complexities. We hypothesized that by manipulating an increase of both cognitive and motor demand, visuomotor behavior would decrease more in individuals with a history of concussion than those without a history of concussion. Twenty females without a history of concussion (age: 21.2 ± 2.16 years) and twenty females with a history of concussion (age: 22.3 ± 2.43 years) quickly and accurately performed a delayed reach to a previously cued location. To control for confounding factors, information was collected regarding the participants’ head injury history, lifestyles, and level of sports participation. The visually guided reaching task was manipulated by varying the complexities of cognitive and motor demand to alter attentional load. As both cognitive and motor load increased, task performance decreased for both groups (p .05). While confounding variables of age, sex, time since last concussion (i.e. acute vs. long-term), stimulant use, sleep patterns, and prescription medication for mood disorders were either controlled or considered during the analysis, participants in the two groups did differ on level of sports participation (p
Keywords: Cognitive Load; Concussion; Long-term; Motor Load; MTBI; Visuomotor Behaviot